Collaboration Improves Student Competence and Creates a Positive Learning Environment - Jamaludin musthofa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The school has 399 students and 21 employees, including four non-teachers and one librarian. The ISR has characteristics like public school in Indonesia where curriculum, policy and finance are supported by Indonesian government and parents’ committee partnership (Setyono, 2016). Based on the concept of No Children Left Behind (NCLB), the ISR need to give opportunities for students to continue to study at they preferred school or university in Indonesia and Saudi Arabia. In these contexts, the community engagement strategies plan is not only collaboration of stakeholders to accommodate learning facilities, but also provide eLearning tools to support the learners need in purpose to improve students’ competencies and create positives learning environment in ISR.